VEGF-targeted magnetic nanoparticles for MRI visualization of brain tumor - Abakumov, Maxim A.; Nukolova, Natalia V.; Sokolsky-Papkov, Marina; Shein, Sergey A.; Sandalova, Tatiana O.; Vishwasrao, Hemant M.; Grinenko, Nadezhda F.; Gubsky, Iliya L.; Abakumov, Artem M.; Kabanov, Alexander V.; Chekhonin, Vladimir P. (Nanomedicine, 2015)
This work is focused on synthesis and characterization of targeted magnetic nanoparticles as magnetic resonance imaging (МRI) agents for in vivo visualization of gliomas. Ferric oxide (Fe3O4) cores were synthesized by thermal decomposition and coated with bovine serum albumin (BSA) to form nanoparticles with Deff of 53±9nm. The BSA was further cross-linked to improve colloidal stability. Monoclonal antibodies against vascular endothelial growth factor (mAbVEGF) were covalently conjugated to BSA through a polyethyleneglycol linker. Here we demonstrate that 1) BSA coated nanoparticles are stable and non-toxic to different cells at concentration up to 2.5mg/mL; 2) conjugation of monoclonal antibodies to nanoparticles promotes their binding to VEGF-positive glioma С6 cells in vitro; 3) targeted nanoparticles are effective in MRI visualization of the intracranial glioma. Thus, mAbVEGF-targeted BSA-coated magnetic nanoparticles are promising MRI contrast agents for glioma visualization. This work focuses on synthesis and characterization of targeted magnetic nanoparticles as magnetic resonance imaging (МRI) agents for in vivo visualization of gliomas. The authors utilize the fact that high-grade gliomas have extensive areas of necrosis and hypoxia, which results in increased secretion of angiogenesis vascular endothelial growth factor (VEGF). Monoclonal antibodies against vascular endothelial growth factor (mAbVEGF) were covalently conjugated to crosslinked BSA coated ferric oxide (Fe3O4) nanoparticles. The results show that these targeted nanoparticles are effective in MRI visualization of the intracranial glioma and may provide a new and promising contrast agent. MRI is one of the most powerful tools for tumor diagnostics, but still it has some limitations, which mostly associated with poor contrast between normal and pathological tissues. One approach to improve contrast in MRI is the use of contrast agent, such as magnetic iron oxide nanoparticles. In this study, we present VEGF-targeted iron oxide nanoparticles that act as glioma targeted T2 contrast agent, which can visualize brain tumor by MRI 24h post intravenous injection. [Display omitted]